Immunology of Modern Society Humans [IMSH] - Shnawa, Ibrahim M. S. (Advances in Social Sciences Research Journal, 2022)
Humans lives in modern society are subjected to an array of factors that impacts the cellularity and functionality of their immune systems. These IMSH factors were ensemble as; Global changes, liberal spread of mental influencing drugs, war warfare ,terrorism ,environmental mutagens and carcinogens as well as environmental allergens .So they are being at risk for both enhancing or dampening effects on their immune systems. Workers have been documenting four main categories of targeted human immune system living at risk of modern society .The IMSH categories are; intravenous drug users, intensive care patients, tumor patients , war warfare and terrorism. The intravenous drug users have shown increase in their humoral B cell immune responses through the elevation of B cell counts and activities and increase in activation markers of T cell subsets. Intensive care patients were mainly showing functionality of cellular immunity like that of ageing immune cells. Tumor patients, however, were found expressing diversity and compositional heterogeneity of immune cell type reaching 33 subsets and marked functional alterations. Tumor microenvironment have shown at least six dominant pan-cancer-classes of dominant immune cells as compared to normal human subjects immune cellularity. Biological warfare and bioterrorism insults were being accompanied by emergence and re-emergence of unfamiliar agent pathogenicity ,seasonality and marked host susceptibility to the terrorism agent necessary need for individual therapy and management ,as well as for pre and post exposure mass vaccination .Each IMSH category have expressed shared and distinctive features. The unified functional insight to the immune systems of human living in modern society is that formed cellular elements of these immune systems behave to different insults in different ways and different elements reacts differently to the same insult.